SOSIALISASI PERKEMBANGAN TEKNOLOGI PERTANIAN DI ERA REVOLUSI INDUSTRI 4.0 DI SMP NEGERI 10 PAGARALAM - Erika, Desta Ria; Padya, Inka Rizki; Aminah, Siti; Martiana, Anggia (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Pagar Alam City is a fairly large producer of agricultural commodities in South Sumatra Province. As producers of vegetables and coffee, many farmers have low education and do not know much about developments in the world of agriculture. The industrial revolution era 1.0 was marked by the presence of mechanical processes using machines. This era is also marked by the energy generated by steam and water. Daily activities that were originally carried out by humans and animals are increasingly being replaced by machines. This service activity can provide benefits for students of SMP Negeri 10 Pagar Alam to increase their knowledge about the industrial revolution 4.0 and introduce technologies used in agriculture and processing of agricultural products.